2016
DOI: 10.26618/ejpbi.v5i2.845
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Debate Technique to Improve Students’ Ability in Speaking

Abstract: This study aimed at finding out the students' speaking skill by using debate.The research design used a pre-experimental, in which it used pre-test and post-test comparison

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…They can also summarize the conclusions of the debate and to respond to other opinions. This study is in line with Baso (2016). There is a significant difference between students' speaking abilities before and after using debate techniques in the speaking process's accuracy.…”
Section: Discussionsupporting
confidence: 89%
“…They can also summarize the conclusions of the debate and to respond to other opinions. This study is in line with Baso (2016). There is a significant difference between students' speaking abilities before and after using debate techniques in the speaking process's accuracy.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, the lecturers are encouraged to use it in teaching speaking. From the results of the study, it can be said that the findings of this study also the same as the studies done by other researchers (Arung, 2016;Baso, 2016;Rubiati, 2010;Widyaningsih, 2016;).…”
Section: E-issn: 2746-380xsupporting
confidence: 89%
“…The results revealed that the use of debate can help EFL learners to improve their speaking skill. In addition, Somagi (2015), Hasanah (2012), andBahria (2013) maintain that debate activities can improve learners' speaking skill. The findings showed that debate activities can offer many opportunities for teachers and their students to develop their abilities and creativity.…”
Section: Students' Oral Presentationmentioning
confidence: 99%